1998
DOI: 10.1038/33402
|View full text |Cite
|
Sign up to set email alerts
|

A cortical representation of the local visual environment

Abstract: Medial temporal brain regions such as the hippocampal formation and parahippocampal cortex have been generally implicated in navigation and visual memory. However, the specific function of each of these regions is not yet clear. Here we present evidence that a particular area within human parahippocampal cortex is involved in a critical component of navigation: perceiving the local visual environment. This region, which we name the 'parahippocampal place area' (PPA), responds selectively and automatically in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

188
2,178
15
10

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,738 publications
(2,391 citation statements)
references
References 21 publications
188
2,178
15
10
Order By: Relevance
“…Overall, the results of our group‐level analyses were consistent with previous studies that observed strong scene‐sensitivity in these regions during standard localiser tasks [Bettencourt and Xu, 2013; Epstein, 2008; Epstein and Kanwisher, 1998; Lee et al, 2008; Spiridon et al, 2006]. Our main scene‐selective contrast revealed significant bilateral activity in each tested ROI at the whole brain level, including HC and TOS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, the results of our group‐level analyses were consistent with previous studies that observed strong scene‐sensitivity in these regions during standard localiser tasks [Bettencourt and Xu, 2013; Epstein, 2008; Epstein and Kanwisher, 1998; Lee et al, 2008; Spiridon et al, 2006]. Our main scene‐selective contrast revealed significant bilateral activity in each tested ROI at the whole brain level, including HC and TOS.…”
Section: Discussionsupporting
confidence: 90%
“…In line with its well established role in scene perception and working memory more broadly [Epstein and Kanwisher, 1998; Ranganath et al, 2004], the greatest degree of inter‐subject overlap (across all ROIs and thresholds) was found in posterior PHG (59%). Further, the region of maximum overlap in the PHG was close to the group‐level peak voxel in the same hemisphere.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…per se, but on underlying cortices in the parahippocampal region (Murray & Mishkin, 1998;Suzuki et al, 1993), with the perirhinal cortex specialized for encoding object representations (Buckley & Gaffan, 1998), the parahippocampal cortex specialized for spatial representations (Epstein & Kanwisher, 1998;Suzuki & Amaral, 1994), and the entorhinal cortex acting to combine input from these two regions to form representations of objects within locations (Suzuki, Miller, & Desimone, 1997).…”
Section: Medial Temporal Lobesmentioning
confidence: 99%
“…was indicated by a nearly complete loss of his internal cognitive map for space during the acute stage of symptoms (Hartley et al., 2003; Howard et al., 2014). An increase in search saccades together with a pronounced deficit in the recognition and incorporation of landmarks were associated with parahippocampal dysfunction (Aguirre et al., 1996; Epstein & Kanwisher, 1998). The pathological changes in gaze behavior and spatial navigation abilities in our patient resembled the pattern of other hippocampal navigation disorders such as MCI‐patients (unpublished data).…”
Section: Introductionmentioning
confidence: 99%